The Group Dynamics of Fish Farmers in Juata Laut Urban Village, North Tarakan, Tarakan - sabransyah sabransyah; muhammad Syafril; Etik Sulistiowati Ningsih (2339-1324, 2024)
This study aimed to identify the profile of fish farmer groups in Juata Laut Urban Village and the level of group dynamics among fish farmers in Juata Laut Urban Village. This study was conducted from July 2022 to May 2023 in Juata Laut Urban Village, North Tarakan, Tarakan. The sample size was 20 respondents using a purposive sampling method. The findings showed that the profile characteristics of fish farmer groups consisted of 5 groups that were formed in 2019, 2020, and 2021 with a different number of members in each group starting from 7 to 15 members and the majority of them were Muslims. The age of whole members in the groups of fish farmers was around 29 to 58 years old. The type of fishing gear used by the groups of fish farmers consisted of 2 different types, namely trawls and gill nets. The level of group dynamics among fish farmers in Juata Laut urban village was categorized as dynamic whereby the group of fish farmers with an estimated score of 63.01 – 81.00; cumulatively, the average score of each group is as follows: 76.5 for Perdana, 72 for Mega Lestari, 76.5 for Imbaya, 72.5 for Intimung, and 74.4for Berkah.